Nutrient Sensing by Hypothalamic Tanycytes - Elizondo-Vega, Roberto Javier; Recabal, Antonia; Oyarce, Karina (Frontiers in Endocrinology, 2019)
Nutritional signals have long been implicated in the control of cellular processes that take place in the hypothalamus. This includes food intake regulation and energy balance, inflammation, and most recently, neurogenesis. One of the main glial cells residing in the hypothalamus are tanycytes, radial glial-like cells, whose bodies are located in the lining of the third ventricle, with processes extending to the parenchyma and reaching neuronal nuclei. Their unique anatomical location makes them directly exposed to nutrients in the cerebrospinal fluid. Several research groups have shown that tanycytes can respond to nutritional signals by different mechanisms, such as calcium signaling, metabolic shift, and changes in proliferation/differentiation potential. Despite cumulative evidence showing tanycytes have the molecular components to participate in nutrient detection and response, there are no enough functional studies connecting tanycyte nutrient sensing with hypothalamic functions, nor that highlight the relevance of this process in physiological and pathological context. This review will summarize recent evidence that supports a nutrient sensor role for tanycytes in the hypothalamus, highlighting the need for more detailed analysis on the actual implications of tanycyte-nutrient sensing and how this process can be modulated, which might allow the discovery of new metabolic and signaling pathways as therapeutic targets, for the treatment of hypothalamic related diseases.